ELASTICITY ANALYSIS OF THE GRAZING AND DETRITAL PATHWAYS IN A SHALLOW PHILIPPINE SEAGRASS MEADOW - Michael Clores (Biotropia: The Southeast Asian Journal of Tropical Biology, 2023)
Ecotrophic efficiency (EE) is an estimate of the proportion of production that is utilized by the next trophic level through direct predation or fishing or exported out of the ecosystem. In seagrass systems, analysis of EE provides crucial information on how biomass, when used or lost in biological functioning, affects the higher trophic levels via death or grazing relative to the energy lost via decomposition (i.e., Flow to the detritus, FTD) and exports to another ecosystem (i.e., Sum of all exports, SAE). In this study, projections on the effect of change in the EE of functional groups in seagrass systems due to the alteration of biomass were established heuristically using Elasticity Analysis. Using a previously constructed Ecopath model for a shallow Philippine seagrass meadow, the simulations of altering the biomass of seagrasses and their grazers were done to determine the change in EE, FTD, and SAE, thereby generating information on the dynamics of the grazing and detrital pathways in the seagrass ecosystem. Results showed the effects of biomass increase and decrease of grazers (herbivorous gastropods, Tripneustes gratilla, and polychaetes). If the grazers’ biomass increases, their EE tends to decrease, and biomass accumulation tends to increase. This implies that a fraction of their production used in the system is reduced even if their predators' density and feeding rate are still constant. In addition, the EE of seagrasses tends to increase, leading to a decrease in biomass accumulation at the primary producers’ trophic level. Lastly, the EE of detritus decreased because the FTD and SAE of its major contributors (the seagrasses) had also decreased. The findings contribute to the ongoing analysis of the role of herbivores versus detritivores in the energetics of seagrass habitats.